Tinjauan Hukum Terhadap Tindak Pidana Lingkungan Hidup; Studi Kasus Kerusakan Hutan di Kalimantan - Yuni Handayani; Ratu Ayu Tiee Teduh; Silvia Damai; Robikhatul Aeni; Ikhwan Aulia Fatahillah (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze law enforcement against environmental crimes through a case study of forest destruction in Kalimantan. This article is a library research using a qualitative approach. The methodology employed is normative legal research presented in a descriptive-analytical manner. The findings reveal that forest destruction in Kalimantan constitutes a systematic and massive environmental crime, yet it has not been met with firm legal enforcement. Obstacles such as weak law enforcement agencies, overlapping authorities, and low public awareness have caused environmental law to lose its coercive power and fail to create a deterrent effect. Therefore, criminal law enforcement must be positioned as a long-term and progressive strategy to achieve sustainable development and ecological justice.